2021
DOI: 10.1111/jasp.12818
|View full text |Cite
|
Sign up to set email alerts
|

It’s not what you do, it’s why you do it: Motives for disclosure and concealment decisions among employees with depression

Abstract: This multi‐method study examined disclosure decisions made by employees with depression as well as their motives for those decisions. In Study 1, we conducted in‐depth interviews with employees who had been diagnosed with depression to better understand why they chose to disclose or conceal their depression at work. Based on the results of the interviews, both approach and avoid motives for disclosure and concealment emerged in the analysis. Further, these motives were influenced by multiple organizational fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 108 publications
(179 reference statements)
1
28
0
Order By: Relevance
“…This work highlights that although online science courses may be perceived as unique and relatively small aspects of students’ college experiences, the benefits students perceived from telling an online science instructor about their depression align with common benefits that individuals with CSIs anticipate across many contexts, including revealing depression to coworkers and family members ( Wisdom and Agnor, 2007 ; Kahn et al. , 2017 ; Follmer and Jones, 2021a , b ). Additionally, it is important to note that two of the benefits students perceived, the instructor gaining an understanding of students’ mental health and fostering a greater connection with the instructor, were more likely to be reported by students who had revealed their depression to instructors.…”
Section: Discussionmentioning
confidence: 75%
“…This work highlights that although online science courses may be perceived as unique and relatively small aspects of students’ college experiences, the benefits students perceived from telling an online science instructor about their depression align with common benefits that individuals with CSIs anticipate across many contexts, including revealing depression to coworkers and family members ( Wisdom and Agnor, 2007 ; Kahn et al. , 2017 ; Follmer and Jones, 2021a , b ). Additionally, it is important to note that two of the benefits students perceived, the instructor gaining an understanding of students’ mental health and fostering a greater connection with the instructor, were more likely to be reported by students who had revealed their depression to instructors.…”
Section: Discussionmentioning
confidence: 75%
“…The review identified 26 studies, including 16 qualitative [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], 7 quantitative [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and 3 mixed-methods studies [ 52 , 53 , 54 ]. Table 1 summarizes the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…All 26 selected studies focused on mental health disclosure; none sought to understand suicidality disclosure. Most of the studies were conducted in Western countries, including the United States [ 31 , 40 , 52 , 53 , 54 ], Australia [ 33 , 34 , 41 , 45 , 48 ], the United Kingdom [ 32 , 44 , 46 , 50 , 51 ], Canada [ 42 , 43 , 47 , 49 ], the Netherlands [ 30 , 35 ], Denmark [ 29 ], New Zealand [ 36 , 37 ] and Germany [ 39 ]. One study was conducted in India [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations